Usefulness of Trabecular CT Attenuation Measurement of Lumbar Spine in Predicting Osteoporotic Compression Fracture: Is the L4 Trabecular Region of Interest Most Relevant?. Issue 3 (1st February 2021) - Lee, Byung-Jou; Koo, Hae-Won; Yoon, Sang Won; Sohn, Moon-Jun
Abstract : Study Design: Retrospective study Objective: The aim of this study was to evaluate the usefulness of computed tomography (CT) attenuation in defining trabecular region-of-interest (t-ROI) at lumbar vertebral body in the assessment of osteoporotic compression fracture (OCF) compared to spinal dual x-ray absorptiometry (DXA). Summary of Background Data: Even though osteoporosis was not diagnosed in the bone mineral density measurement using DXA, we often experienced cases where the screw was weakly inserted due to low bone quality during screw insertion. Methods: A total of 188 patients who met the inclusion criteria were enrolled. We determined best cutoff value of the simple t-ROI attenuation at the most relevant level for predicting OCF. We assessed correlations between the simple t-ROI attenuation at the most relevant level and OCF rate, and investigate the association between the number of compression fracture and simple t-ROI attenuation at the most relevant level. Results: L4 ROI attenuation is the most accurate measurement for predicting osteoporotic compression fracture with an area under the curve of 0.798. The optimal cutoff point of L4 ROI attenuation was measured at 90.5 HU with 88.8% and 60.6% sensitivity and specificity, respectively. L4 ROI attenuation was significantly correlated with the osteoporotic compression fracture rate ( r = −0.545, P < 0.001). The number of compression fracture (coefficient of determination R2 = 0.286; P < 0.001) was independently correlated with L4 ROI attenuation. Conclusion: Simple t-ROI computed tomography attenuation is an accurate measurement tool in predicting OCF compared to DXA T-score. The value of L4 t-ROI attenuation is the most relevant measurement for predicting osteoporotic compression fracture, is an alternative to DXA, and can predict the number and rate of compression fractures. Spine surgeons should be aware of L4 t-ROI attenuation to make successful fusion in spine surgery for elderly patients group. Level of Evidence: 3 Abstract : Simple trabecular region-of-interest computed tomography attenuation is an accurate measurement tool in predicting osteoporotic compression fracture compared to dual x-ray absorptiometry (DXA) T-score. The value of L4 t-ROI attenuation is the most relevant measurement for predicting osteoporotic compression fracture, is an alternative to DXA, and can predict the number and rate of compression fractures